A Universal Interface Layer Based on an Amine‐Functionalized Fullerene Derivative with Dual Functionality for Efficient Solution Processed Organic and Perovskite Solar Cells. Issue 8 (21st January 2015) - Azimi, Hamed; Ameri, Tayebeh; Zhang, Hong; Hou, Yi; Quiroz, Cesar Omar Ramirez; Min, Jie; Hu, Mengyao; Zhang, Zhi‐Guo; Przybilla, Thomas; Matt, Gebhard J.; Spiecker, Erdmann; Li, Yongfang; et al.
<x xml:space="preserve">Abstract</x> The successful application of an effective dipolar interface layer based on an amine functionalized fullerene derivative (DMAPA‐C60) is reported for the perovskite and organic photovoltaic devices. The incorporation of DMAPA‐C60 facilitates a favorable energy level alignment, and results in enhanced mobility‐lifetime (µt) product.